2000
DOI: 10.1128/jcm.38.12.4523-4526.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Coronavirus Isolated from a Diarrheic Foal

Abstract: A coronavirus was isolated from feces of a diarrheic foal and serially propagated in human rectal adenocarcinoma (HRT-18) cells. Antigenic and genomic characterizations of the virus (isolate NC99) were based on serological comparison with other avian and mammalian coronaviruses and sequence analysis of the nucleocapsid (N) protein gene. Indirect fluorescent-antibody assay procedures and virus neutralization assays demonstrated a close antigenic relationship with bovine coronavirus (BCV) and porcine hemagglutin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
135
0
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(148 citation statements)
references
References 25 publications
2
135
0
11
Order By: Relevance
“…Apoptosis represents an important antivirus defense mechanism of the host cell, and viruses have evolved strategies to counteract and regulate apoptosis in order to maximize the production of virus progeny and promote the spread of virus progeny to neighboring cells. ECoV was isolated from the feces of a diarrheic foal, and investigations revealed that it was genetically similar to BCoV (Guy et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apoptosis represents an important antivirus defense mechanism of the host cell, and viruses have evolved strategies to counteract and regulate apoptosis in order to maximize the production of virus progeny and promote the spread of virus progeny to neighboring cells. ECoV was isolated from the feces of a diarrheic foal, and investigations revealed that it was genetically similar to BCoV (Guy et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In in vitro cultures, human rectal adenocarcinoma (HRT-18) cells were used for propagation of ECoV, but this cell line could not induce a distinctive CPE (Guy et al, 2000). In our preliminary investigation, we found that MDBK cells (a bovine kidney-derived cell line) infected with ECoV showed more distinctive morphological changes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Currently, group 2 CoVs are organised into bovine-like (subgroup 2a) and severe acute respiratory syndrome (SARS)-like (subgroup 2b) viruses. Members of subgroup 2a are bovine coronavirus (BCoV), mouse hepatitis virus (MHV), rat coronaviruses, porcine haemagglutinating encephalomyelitis virus (PHEV), human coronavirus (HCoV) OC43, human enteric coronavirus (HECV) 4408 (Enjuanes et al, 2000), and the newly recognised equine coronavirus (ECoV) (Guy et al, 2000), HCoV-HKU1 (Woo et al, 2005) and canine respiratory coronavirus (CRCoV) (Erles et al, 2003). SARS-CoV, initially defined as prototype of a new group 4, has been placed more recently within group 2 CoVs, in a subgroup 2b, together with SARS-like CoVs isolated from bats and wild carnivores (Gorbalenya et al, 2004;Weiss and Navas-Martin, 2005).…”
Section: Coronavirus Taxonomy and Genomic Organisationmentioning
confidence: 99%
“…Currently, CoVs are classified into three different genetic and antigenic groups with group 2 being further divided into subgroups 2a and 2b. Subgroup 2a consists of mouse hepatitis virus, rat sialodacryadenitis virus, human coronavirus (HCoV) HKU1 (Woo et al, 2005) and several bovine-like CoVs, including bovine coronavirus (BCoV), porcine haemagglutinating encephalomyelitis virus (PHEV), HCoV-OC43, human enteric coronavirus (HECoV) 4408 (Enjuanes et al, 2000), and the newly recognized equine coronavirus (ECoV) (Guy et al, 2000) and canine respiratory coronavirus (CRCoV) (Erles et al, 2003;Decaro et al, 2007). There are multiple genetic and antigenic evidences that several subgroup 2a CoVs, such as HCoV-OC43, HECoV-4408, PHEV and CRCoV, have arisen as consequence of trans-species infections caused by BCoV (Zhang et al, 1994;Vijgen et al, 2005Vijgen et al, , 2006Erles et al, Veterinary Microbiology 145 (2010) [245][246][247][248][249][250][251] Recently, a coronavirus strain (179/07-11) was isolated from water buffalo (Bubalus bubalis) and the virus which displayed a strict genetic and biological relatedness with bovine coronavirus (BCoV) was referred to as bubaline coronavirus (BuCoV).…”
Section: Introductionmentioning
confidence: 99%